Electronic Roulette Wheel / Norzamlan Kamarulzaman and Aswadi Abdullah - Kamarulzaman, Norzamlan (2006)
A Electronic Roulette Wheel is a digital electronic devices. It is primarily used to do execute random selection. This report shows how the circuit diagram is created, and simulate by using the circuit maker. Our project uses a 9V battery, IC 555 (timer), IC 74154 (decoder), IC 7493 (counter), IC 7805 (regulator), Resistor, Capacitor, Diode, LED’s in addition to standard